Controlling urban stormwater pollution by constructed wetlands: a Canadian perspective. (28th September 2007) - Crowe, A.S.; Rochfort, Q.; Exall, K.; Marsalek, J.
During the past 20 years, Constructed Stormwater Wetlands (CSWWs) have attained broad acceptance in Canada as effective measures for stormwater management. CSWWs are used mainly for improving stormwater quality by providing sufficient treatment volumes in shallow permanent pools. This leads to high requirements for land, which is one of the constraints on CSWWs use. Even though CSWWs perform less effectively in cold weather, through proper design they can be kept operational through the winter months. CSWWs attract wildlife, but do not provide high quality habitat. Consequently, CSWWs and their effects on wildlife need to be monitored and ecotoxicological risks controlled.